ANALISIS PENGADAAN BAHAN BAKU DAN PRODUKSI PADA INDUSTRI RUMAH TANGGA ROTI BAKAR BANDUNG NUKASEP DI PASAR PEDATI KABUPATEN BENGKULU TENGAH - Sintiya; Yulihartika, Rika Dwi; Fariadi, Herri (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2024)
One of the household industries in Central Bengkulu Regency is the Bandung Nukasep Bakar Roti making business which produces every day. This research aims to determine the procurement of raw materials for Bandung Nukasep Toast and to find out what the production factors are for Bandung Nukasep Toast at Pedati Market, Central Bengkulu Regency. The method used in this research is descriptive qualitative where data is obtained from observation, interviews and secondary data. Based on the research results and theories underlying the problems discussed, the procurement of raw materials for Bandung Nukasep Toast at Pedati Market, Central Bengkulu Regency applies the six right components, namely right quantity (the number of toasts produced every day is an average of 312 packs), right quality (twin cakra brand flour), right place (purchase location of raw materials at the sari spice shop Pasar Minggu, Bengkulu City), on time (once a week), right price (for one purchase of Rp. 6,262,000), and right type (using high protein flour). And the production factors for Bandung Nukasep Toast at Pasar Pedati, Central Bengkulu Regency include raw materials, capital, labor, length of business, and demand.